Tajwino shortcut to expert tajweed al-quran - Mohamed Khirul Nizzuan, Akmal Hazim; Azhar, Nur Aida Syamimi; Basir, Aqilah; Che Hashim, Nur Hanis Ayuni; Sabaruddin, Siti Nor Azimah (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
These days, most Muslims are not practical in the study of tajweed to have a proper recitation of alQuran. This is because of less encouragement in the study of tajweed rules and uninteresting teachingaids to help this study. Hence, this is where the innovation of Tajwino based on the UNO card game will play its role in helping Muslims to have better approach in studying tajweed as it makes teaching and learning process much more fun. The first objective of this study is to enhance and memorise Tajweed rules easily. This product focuses on ‘Nun Sakinah and Tanwin’ rules which is the basics rule for everyone to know in order to recite al-Quran which are Ikhfa’ Hakiki, Izhar Halqi, Idgham Maal Ghunnah, Idgham Bila Ghunnah and Iqlab. However, this product also can help in studying the rules of Mad Wajib Muttasil, Mad Jaiz Munfasil, Idgham Mislain Syafawi, Ikhfa Syafawi,Izhar Syafawi, Qalqalah Kubra, Qalqalah Sughra ,Mad Silah Tawilah,Mad Silah Qasirah, Mad Lin, Mad Iwadh dan Mad Aridh Lissukun. These are the other rules which can be played in Tajwino as it functions as a wild card. Tajwino will act as an interesting teaching aid that is suitable to be used for all people regardless of age. Therefore, the second objective of this product is to act as learning materials especially for teachers. Moving forward, parents can also use this product as way to attract children in studying tajweed rules. The process of learning while playing will supposedly be much easier and efficient if it was collaborated with a game that build up the mind.